Investigations of hollow carbon nanoshell structures - Watts, Julie A. (2019)
Discrete, uniform < 10 nm sized hollow carbon nanoshells (HCNS) have been formed via a facile, one-step heat induced transformation of alkane thiol stabilised silver nanoparticles (AgNP). Direct evidence for the templated formation of predominantly complete, spherical HCNS, from rapid heating to > 650 °C, in situ inside a transmission electron microscope with a microelectromechanical system (MEMS) system is presented, with the size of the resultant HCNS being slightly larger than that of the AgNP template. Further, ex situ heating of AgNP on carbon nanotube supports has revealed the defining features of these very stable HCNS structures: hollow interiors and very thin graphitised, yet highly disordered walls.